#### Answer

$S(t)$ = $(f\circ g\circ h)(t)$ for
$h(t)=\cos t,$
$g(t)=\sin t$, and
$f(t)=t^{2}$

#### Work Step by Step

$(f\circ g\circ h) (t)=f[g(h(t))]$
If we used a calculator, step by step,
for each step,
define the operation we would perform on the current result.
Starting with $t$, we would
1. calculate the cosine of t ,$\ \ h(t)=\cos t$
2. calculate the sine of current result, $\ \ g(x)=\sin t$
3. square the current result , $\ \ f(t)=t^{2}$
$S(t)$ = $(f\circ g\circ h)(t)$ for
$h(t)=\cos t,$
$g(t)=\sin t$, and
$f(t)=t^{2}$